Patterns in China's use of force : evidence from history and doctrinal writings - Burles, Mark, 1970-; Shulsky, Abram N.; Rand eBooks (Santa Monica, CA : RAND, 2000)
The People's Republic of China has often used force in ways that surprised and perplexed other countries. The Chinese appear to believe that, by carefully designing military operations to achieve maximum political effect, they can successfully use force even when the overall military balance is unfavorable. China's past successes in using force in this way while avoiding a massive reaction from its adversaries may give it confidence that it can succeed in the future as well. And China may feel that it can afford to accept greater risks. Many of the past uses of force occurred when China either was not a nuclear power or did not have a secure nuclear second-strike capability. The possession of strategic nuclear weapons may enable the Chinese leadership to run risks that it otherwise could not. This is tempered however, by the facts that China ran its past risks when it had some degree of support from one superpower against the other and that, after decades of economic development, China now has more to lose if it underestimates the risks.
"Project Air Force."
Includes bibliographical references (p. 95-106).
Also available on the internet via WWW in PDF format.
Keywords: Military art and science -- China -- History; Military doctrine -- China -- History; Strategy; China -- Defenses; China -- History, Military -- 1949-; China -- Military policy; China -- Military relations -- United States; Electronic books